Administrative factors affecting the performance effectiveness of private vocational education institutions in Bangkok, under the Malcolm Baldrige National Quality Award’s criteria - Sivageerattana, Supaporn; Trakool Meechai, Trakul (Journal of Rattana Bundit University, 2021)
This research aimed to 1) study the level of administrative factors of private vocational education institutions in Bangkok, 2) study the performance effectiveness level of private vocational education institutions in the Bangkok area based on the criteria of the Malcolm Baldrige National Quality Award, and 3) study administrative factors affecting the performance effectiveness of private vocational education institutions in Bangkok, under the Malcolm Baldrige National Quality Award’s criteria. The respondents of this study include 228 participants of administrators, teachers, and educational personnel of 57 private vocational education institutions in Bangkok. Participants were selected by simple probability sampling by simple random sampling method. A set of survey questionnaires drew the study’s data. A packaged program for social research analyzed data. The statistical analysis methods applied to this research comprise descriptive statistics such as percentage, means, standard deviation, and inferential statistics such as Pearson product-moment correlation coefficients and hierarchical multiple regression analysis. The study results showed the following aspects. 1) The level of administrative factors of private vocational education institutions in Bangkok is relatively high. 2) The level of performance effectiveness of private vocational education institutions Bangkok area based on the Malcolm Baldrige National Quality Award’s criteria is relatively high. 3) The administrative factors that could be used to predict the performance effectiveness under the Malcolm Baldrige National Quality Award’s criteria of private vocational education institutions in Bangkok is at the percentage of 86.0. The factors that could explain the variance in performance effectiveness of the private vocational education institutions in Bangkok were the policy of administration and practices (86%), personnel characteristics (68.20%), environmental factors (67.30%), and organizational factors (60.80%) respectively.